The Radicalization of Neoliberalism in Brazil and the Role of the Ministry of Tourism in Coalition Presidentialism - Carolina Todesco; Rodrigo Cardoso da Silva (Via@)
Based on the premise that the government system influences the institutional capacity of official tourism bodies, policies and public investments, the study aims to analyze how the Brazilian Ministry of Tourism was co-opted by coalition presidentialism in ultra-liberal governments, from 2016 to 2022, focusing on the distribution of ministerial positions and budget control by political parties. The research was based on the theoretical framework of political science regarding coalition presidentialism and carried out documentary research, with the cross-referencing of data regarding composition of coalition parties, parliamentary amendment by political party, political party in charge of the body, and budget executed. The results indicate that the Brazilian Ministry of Tourism remained in the government structure during the ultra-liberal governments, which defended the streamlining of the state machine, as it fulfilled the role of accommodating allied political parties, configuring itself as an instrument to meet parliamentary demands and assist the coalition of governments in Congress. Coalition presidentialism is not a reality exclusive to Brazil, which highlights the need for research that can compare the influence of similar and different government systems on tourism governance.